Integrasi Tamadun Melayu dalam Kurikulum Madrasah Ibtidaiyah sebagai Upaya Penguatan Pendidikan Karakter - Susiandri; Jasril; Umara, Alifiyoni Rahmat; M. Muda (Journal of Practice Learning and Educational Development, 2026)
Character education has become a major focus in basic education, including in Madrasah Ibtidaiyah (MI), in line with the increasing moral and social challenges faced by students in the era of globalization. One relevant approach to strengthening character is the integration of local wisdom values, particularly Malay civilization, into the learning curriculum. Malay civilization contains noble values such as religiosity, politeness, mutual cooperation, responsibility, and respect for customs and the social environment. This study aims to describe the integration of Malay civilization into the Madrasah Ibtidaiyah curriculum as an effort to strengthen students' character education. The research used a qualitative approach with a case study design. Data collection techniques included learning observation, interviews with teachers and madrasah principals, and documentation of learning tools and school activities. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results show that the integration of Malay civilization values into the MI curriculum can be done through the development of teaching materials, contextual learning strategies, school cultural habits, and teacher role models. This integration has been proven to contribute to strengthening students' religious character, discipline, responsibility, and social awareness. Thus, Malay civilization can be an effective cultural foundation in supporting character education at Madrasah Ibtidaiyah.